ASSESSMENT OF CLIMATE CHANGE AWARENESS AND ADAPTATION BY SUGARCANE FARMERS IN GANYE LOCAL GOVERNMENT AREA, ADAMAWA STATE, NIGERIA - Yohanna. L; Ezra A; Sini. E. D; Yakubu. L. T, (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2018)
The study assessed the awareness and adaptation strategies by sugar cane farmers in Ganye Local Government area Adamawa State. A multi-location sampling technique was used to select 50 Sugar cane farmers from the local government area. Primary data collected from the farmers included: the socioeconomic characteristics of the farmers such as gender, age and educational qualification as well as climate change awareness and adaptation strategies. The data were analysed using descriptive statistic. The result shows that majority of the farmers in the state are aware of the climate change despite the low level of education by the farmers and submitted that climate change has severe effect on their farming activities. The effect identified include reduce crop yield, high temperature, drought while excessive rainfall and high winds directly destroy crops. The farmers are trying their efforts to adapt to climate change in some ways such as planting fast growing trees surrounding their sugar cane farm to reduce effects of wind and flooding which have greater effect on sugarcane farming, planting early maturing varieties and crop diversification among others. In other to improve sugarcane farming in the study area, farmers literacy programme should be introduce among the sugarcane farmers, this will help in understanding the contemporary issues on climate threat to agriculture, government should provide functional market system to the rural community. This will ease the cost of transport and damage of the crops, also provision of modern farm implements that will aid in sugarcane farming and also information on adaptation measures should be provided to the farmers.